Wheezing in Children Under 5 Years - Rai, Basant; Khanal, Sagun; Chaudhary, Shipra (Journal of Nobel Medical College, 2026)
Background: Wheezing is a common characteristic feature of lower respiratory tract infection in children. This study was to assess the clinical characteristics, diagnostic pattern, treatment modalities and outcome of children presenting with wheezing. Materials and Methods: The data were collected retrospective from hospital records. We reanalyzed by using the Statistical Package for the social Sciences (SPSS) version 21. Children with wheeze associated lower respiratory tract infection among children between 2 to 60 months of age over a period of one year. Data were analyzed using descriptive and inferential statistics. Results: The prevalence of wheezing in children admitted in hospital with lower respiratory infection was 77.05%. Among 272 cases, 73.16% were male and infants were 66.91%. Cough and fever were most common presenting symptoms. Common risk factors were prior history of wheezing, caesarean delivery at birth, underweight and lack of exclusive breast feeding. Twenty five percent cases had crepitations/crackles along with wheezing. Antibiotics were used in 91.54% and supplemental oxygen was needed in 41.91%. Most common final diagnosis was acute bronchiolitis and wheeze associated lower respiratory infection followed by pneumonia. Outcome was improved in 96.69% patients. Conclusion: Wheezing was the common clinical finding among children. Infant and male had significant wheezing. There was a significant conformity association between a recurrent wheezing phenotype. Children with wheezing had short hospital stay with the good outcome.